2019
DOI: 10.4236/aasoci.2019.97023
|View full text |Cite
|
Sign up to set email alerts
|

The Value of E-Sports Is in the Eye of the Beholder, But Can E-Sports Operators Influence What the Spectators See?

Abstract: This article considers the societal discussion revolving around e-sports to be a reflection of the incommensurability of different means of value justification. The article seeks an answer to the question of how e-sports operators can demonstrate that their work entails aspects, i.e. propose value to aspects that are generally valued. The article presents a theory-guided analysis of the means of value justification in the world of e-sports. The theoretical basis builds upon modern economic sociology. The estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…If there are some national leagues in esports, most of them involve more than one country or are even worldwide, consistent with the idea that esports communities are not bound by national borders or time zones (Jalonen 2019). A key difference between sports and esports is when they were established.…”
Section: The Organisation Of a National Leaguesupporting
confidence: 62%
See 2 more Smart Citations
“…If there are some national leagues in esports, most of them involve more than one country or are even worldwide, consistent with the idea that esports communities are not bound by national borders or time zones (Jalonen 2019). A key difference between sports and esports is when they were established.…”
Section: The Organisation Of a National Leaguesupporting
confidence: 62%
“…In the nascent literature on esports, there is not much research focusing specifically on economics. However, contributions by Mangeloja (2019), Parshakov (2019), and Ward and Harmon (2019) represent exceptions, together with some non-economic publications referring to economic aspects, e.g., Abanazir (2019) and Jalonen (2019). These five recent publications were used as start set.…”
Section: Results: Do the Main Peculiar Economics Of Professional Teammentioning
confidence: 99%
See 1 more Smart Citation
“…It is laterally shown that the mutual penetration between e-sports and secondary elements is relatively deep. The social aspect of online gaming and the following discussion of may reinforce the self-esteem of the players as well as the fans, which means a sense of accomplishment to an adolescent's life [2].…”
Section: Fig2 the Pattern Of Consumption Of The E-sports Usersmentioning
confidence: 99%
“…Although the studies mentioned were conducted only with athletes from traditional sports [21,22], the fact that eSports presents similar psychological demands [23] leads us to assume that, whether in electronic sports or traditional sports, the athletes' experience is significantly influenced by the coach's motivational environment [24], and it is necessary to investigate this premise. The eSport players' perceptions of the degree to which their coach-created climate is empowering and disempowering could provide a better understanding of the characteristics that favour or hinder the sporting experience, enabling the creation of healthier and more-adaptive motivational climates in the context represented by eSports [25].…”
Section: Introductionmentioning
confidence: 99%